Способ переработки облученного ядерного топлива - Кудрявцев Е. Г. Евгений Георгиевич; Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Меркулов И. А. Игорь Александрович; Бондин В. В. Владимир Викторович; Волк В. И. Владимир Иванович; Бычков С. И. Сергей Иванович; Алексеенко В. Н. Владимир Николаевич
опубл. 20.08.12